Implementation of a safer conception programme for HIV- affected men and women in rural Uganda - Matthews, Lynn T.; Owembabazi, Moran; Tukwasibwe, Deogratius; Najjuma, Alice; Muyindike, Winnie; Tumwine, John Mary; Hornstein, Benjamin; Bassler, John; Long, Dustin; Gill, Elizabeth; Young, Cynthia; Chitneni, Pooja; et al. (Global Public Health, 2024)
We integrated safer conception care into a Ugandan HIV clinic. People with HIV (PWH), or partnered with a PWH, and desiring children were eligible for the Healthy Families Clinic Program. Clients completed quarterly safer conception counselling visits and questionnaires to provide information around method preferences and outcomes (partner pregnancy, partner seroconversion). We used clinic level data to evaluate longitudinal viral suppression among PWH. Between November 2016 and January 2020, 361 clients (53% men) accessed services. 75% were PWH (51% women, 96% men): 99% were on antiretroviral therapy (ART) and most reported HIV-sero-different partnerships (97%). Frequently selected safer conception methods included ART (86%), timed condomless sex (74%), and PrEP (40%) with important differences by HIV-serostatus and gender. 22.5% reported pregnancy. Most (97%) PWH were virally suppressed at enrolment and 81% of non-virally suppressed PWH were virally suppressed at 15 months. Two HIV-negative clients (2%) had HIV seroconversion. There is demand for safer conception care in a public sector HIV-clinic in Uganda. Men and women have unique safer conception care preferences. The majority of clients engaged in safer conception care had viral suppression at follow up.
Keywords: Uganda; HIV; Safer conception; Treatment as prevention; PrEP